Reporting heterogeneity in self-assessed health among elderly Europeans - Christian Pfarr; Andreas Schmid; Udo Schneider (Health Economics Review, 2012)
Introduction: Self-assessed health (SAH) is a frequently used measure of individuals' health status. It is also prone to reporting heterogeneity. To control for reporting heterogeneity objective measures of true health need to be included in an analysis. The topic becomes even more complex for cross-country comparisons, as many key variables tend to vary strongly across countries, influenced by cultural and institutional differences. This study aims at exploring the key drivers for reporting heterogeneity in SAH in an international context. To this end, country specific effects are accounted for and the objective health measure is concretized, distinguishing effects of mental and physical health conditions. Methods: We use panel data from the SHARE-project which provides a rich dataset on the elderly European population. To obtain distinct indicators for physical and mental health conditions two indices are constructed. Finally, to identify potential reporting heterogeneity in SAH a generalized ordered probit model is estimated. Results: We find evidence that in addition to health behaviour, health care utilization, mental and physical health condition as well as country characteristics affect reporting behaviour. We conclude that observed and unobserved heterogeneity play an important role when analysing SAH and have to be taken into account.
Keywords: 330; reporting heterogeneity; SHARE; generalized ordered probit